Prevalence of anaemia among adolescents in rural area of North Karnataka - Deepti Shettar; Bhavana Hiremath; Basavaraj Yamakanamardi; Raveendra D. Totad (Al Ameen Medical College, 2024)
Background: Worldwide there are more than 1.2 billion adolescents, more than half of all adolescents live in Asia. Anemia is one of the most common health conditions contributing to morbidity among adolescents. Hence, this study was undertaken to know the prevalence of anemia among adolescents. Objective: To assess the prevalence of anaemia among adolescent boys and girls in rural area. Methods: A community based, cross sectional study was conducted among 600 adolescents in rural area of Dharwad. Data was collected using semi-structured questionnaire consisting of demographic details. Hemoglobin estimation was done by Sahli's method. Data was analyzed using SPSS v21.0. Results: Among the total 600 adolescents, 60.66% were found to be anemic of whom 14.8% had mild, 43.7% moderate and2.2% had severe anemia. Hemoglobin level was significantly different among boys and girls (p=<0.0001). Conclusion: Prevalence of anaemia was higher among adolescent girls than boys. Factors such as age of the participants, sex, marital status, father's education, mother's education, father's occupation and socio-economic status were significantly associated with anemia in adolescents.